Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Penghindaran Pajak dengan Ukuran Perusahaan Sebagai Variabel Kontrol - Sharasanti, Diah Anugrah; Tjahjono, Josephine Kurniawati; Harjanto, Gloria Mariana Kristanti (ITB AAS INDONESIA, 2025)
This study aims to examine the effect of financial performance ratios (liquidity, Leverage, and Profitability) on management decisions in conducting tax avoidance with firm size as the control variabel. This study is a modification of the research of Harjanto & Tjahjono (2025), by taking the same data, but different analysis techniques. The population taken is Corporate Taxpayers registered at the North Makassar Pratama Tax Office who have reported Surat Pemberitahuan Pajak (SPT) in 2021 to 2023 and are included in the Makassar Industrial Area (KIMA), and 209 samples were taken using purposive sampling technique. Statistical testing using IBM SPSS software version 25, and it was found that the liquidity variabel did not have a significant effect on tax avoidance, while leverage and profitability had a positive effect. Firm size as a control variabel did not affect tax avoidance, which proves that management decisions in conducting tax avoidance are not related to the size of the company, but rather the decision on how to minimize the amount of tax burden so that the resulting profit will be optimal